2019
DOI: 10.1371/journal.pone.0218422
|View full text |Cite
|
Sign up to set email alerts
|

Cost utility analysis of end stage renal disease treatment in Ministry of Health dialysis centres, Malaysia: Hemodialysis versus continuous ambulatory peritoneal dialysis

Abstract: ObjectivesIn Malaysia, there is exponential growth of patients on dialysis. Dialysis treatment consumes a considerable portion of healthcare expenditure. Comparative assessment of their cost effectiveness can assist in providing a rational basis for preference of dialysis modalities.MethodsA cost utility study of hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) was conducted from a Ministry of Health (MOH) perspective. A Markov model was also developed to investigate the cost effectivenes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, it could also be due to the absence of a true difference between both modalities [5,19]. Given that PD as an initial dialysis modality was found to be more cost-effective than HD [20], the finding from this study, if confirmed, further strengthens the argument for the increased use of PD in the local setting. Unsurprisingly, it was found that older age and the presence of DM were significantly associated with poorer survival.…”
Section: Discussionsupporting
confidence: 52%
“…However, it could also be due to the absence of a true difference between both modalities [5,19]. Given that PD as an initial dialysis modality was found to be more cost-effective than HD [20], the finding from this study, if confirmed, further strengthens the argument for the increased use of PD in the local setting. Unsurprisingly, it was found that older age and the presence of DM were significantly associated with poorer survival.…”
Section: Discussionsupporting
confidence: 52%
“…For example, in Thailand, the universal coverage system followed a PD-first policy, which has resulted in a steady increase in PD uptake over time. 20 In addition to cost savings, promoting PD use could also improve access to dialysis in rural areas in countries where the funding models favor urban settings for HD centers, as described in Malaysia 21 and Indonesia. 22 Compared with the dominant public funding system for CKD care globally, government funding was responsible for nondialysis CKD care in only a third of OSEA countries and for KRT in 60% of countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the result, they found that the second eye cataract surgery resulted in USD2,727 per QALY gained compared to unilateral pseudophakia [46]. A study by Surendra et al [47] in Malaysia compared the CUA for 2 types of interventions: hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) for end-stage renal disease (ESRD) patients. The authors reported that the difference was RM46595 per QALY gain for HD and RM41,527 for CAPD.…”
Section: Economic Evaluation -Cost-utility Analysis (Cua)mentioning
confidence: 99%